Current perspectives on clinical use of exosomes as novel biomarkers for cancer diagnosis - Yi, Xiaomei; Chen, Jie; Huang, Defa; Feng, Shuo; Yang, Tong; Li, Zhengzhe; Wang, Xiaoxing; Zhao, Minghong; Wu, Jiyang; Zhong, Tianyu (Frontiers in Oncology, 2022)
Exosomes are a heterogeneous subset of extracellular vesicles (EVs) that biogenesis from endosomes. Besides, exosomes contain a variety of molecular cargoes including proteins, lipids and nucleic acids，which play a key role in the mechanism of exosome formation. Meanwhile, exosomes are involved with physiological and pathological conditions. The molecular profile of exosomes reflects the type and pathophysiological status of the originating cells so could potentially be exploited for diagnostic of cancer. This review aims to describe important molecular cargoes involved in exosome biogenesis. In addition, we highlight exogenous factors, especially autophagy, hypoxia and pharmacology, that regulate the release of exosomes and their corresponding cargoes. Particularly, we also emphasize exosome molecular cargoes as potential biomarkers in liquid biopsy for diagnosis of cancer.